Discovery of novel chemoeffectors and rational design of Escherichia coli chemoreceptor specificity - Bi, Shuangyu; Yu, Daqi; Si, Guangwei; Luo, Chunxiong; Li, Tongqing; Ouyang, Qi; Jakovljević, Vladimir; Sourjik, Victor; Tu, Yuhai; Lai, Luhua (Proceedings of the National Academy of Sciences of the United States of America, 2013)
Bacterial chemoreceptors mediate chemotactic responses to diverse stimuli. Here, by using an integrated in silico, in vitro, and in vivo approach, we screened a large compound library and found eight novel chemoeffectors for the Escherichia coli chemoreceptor Tar. Six of the eight new Tar binding compounds induce attractant responses, and two of them function as antagonists that can bind Tar without inducing downstream signaling. Comparison between the antagonist and attractant binding patterns suggests that the key interactions for chemotaxis signaling are mediated by the hydrogen bonds formed between a donor group in the attractant and the main-chain carbonyls (Y149 and/or Q152) on the α4 helix of Tar. This molecular insight for signaling is verified by converting an antagonist to an attractant when introducing an N-H group into the antagonist to restore the hydrogen bond. Similar signal triggering effect by an O-H group is also confirmed. Our study suggests that the Tar chemoeffector binding pocket may be separated into two functional regions: region I mainly contributes to binding and region II contributes to both binding and signaling. This scenario of binding and signaling suggests that Tar may be rationally designed to respond to a nonnative ligand by altering key residues in region I to strengthen binding with the novel ligand while maintaining the key interactions in region II for signaling. Following this strategy, we have successfully redesigned Tar to respond to l-arginine, a basic amino acid that does not have chemotactic effect for WT Tar, by two site-specific mutations (R69′E and R73′E).
Gesehen am 25.11.2020